1421 The Importance of Ir-Homa and Wthr in the Prediction of the Development of Metabolic Syndrome (MS). (October 2012) - Grimaldi, A; Mosca, A; Piedimonte, A; Guttadoro, D; Podagrosi, M; Mercurio, R; Giacomini, A; Caiazzo, AM; Papa, RE; Vania, A
Abstract : Background and Aim: Globesity has made visible the increased risk, yet among youngsters, of cardiovascular diseases, NAFLD, MS.(1)(2) The Aim: of this study is to stress how two simple indexes (IR-HOMA and WtHR(3) ) can be useful at out-patients level to detect the presence of an often still unidentified MS. Methods: 857 ow/ob children (405 female, 47.26%), aged 10.54±2.87, were included in this retrospective (5 years) study. Results: The standard risk factors of MS (NCEP ATP III modified) in the studied population were represented as follows: Waist Circumference ≥90°c 62.40%; Hypertension 21.52%; Triglycerides >95°c 12.34%, HDL < 5°c 5.52%, Glycaemia ≥100mg/dl 4.72%; besides, 34.64% showed IR-HOMA >2.5. The overall MS prevalence was 5.49%. Due to an OR=5.29 (p<0.05) for IR-HOMA vs. MS factors, all patients with an IR-HOMA >2.5 are very likely to have 3 or more elements of MS. If both IR-HOMA and WtHR are abnormal, OR becomes 6.24 (p<0.05). Conclusions: In the ow/ob child, IR-HOMA and WtHR are important anticipating factors of MS, even at a very young age, much below the age of 10, presently considered the lowest age to diagnose such complication. This stresses once again how, in any case of obesity, an early intervention is needed, in order to prevent the development of cardiovascular disease in early adult age.(1) Monereo Megías S et al. Endocrinologia y Nutricion, 2012. 59:155–159. Saffari F et al. Therapy Clinical Risk Managment. 2012. 8:55–63. Maffeis C et al. J Pediatr. 2008; 152:207–13.